2010
DOI: 10.4040/jkan.2010.40.5.650
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Workplace Violence on Work-related Anxiety and Depression Experience among Korean Employees

Abstract: Purpose: Work-related anxiety and depression are frequent work-related mental health problems. In this study the relationship between workplace violence and work-related anxiety and/or depression among Korean employees was evaluated. Methods: Data were obtained from the Korean Working Condition Survey of 2006. Participants were 9,094 Korean workers aged 15-64 yr. Multiple logistic regression using SAS version 9.1 was used. Results: The incidence of work-related anxiety, work-related depression and workplace vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
(1 reference statement)
3
13
2
Order By: Relevance
“…In addition, the nurses who are informally employed are less likely to experience stress and anxiety than the nurses who are formally employed. The type of employment is associated with workplace anxiety (31). It seems that informally employed nurses can quit their jobs more easily because they have no obligation to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the nurses who are informally employed are less likely to experience stress and anxiety than the nurses who are formally employed. The type of employment is associated with workplace anxiety (31). It seems that informally employed nurses can quit their jobs more easily because they have no obligation to the organization.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of suicides among Korean service workers13 ) and high suicide mortality in other countries14 ) reflect how much service workers suffer from stressful events related to experience of depression and anxiety symptoms. Workplace violence is the most severe stressful event experienced by service workers15 ) , and it is also related to depression and anxiety16 ) . Our current study demonstrates that Engaging with Complaints is related to experience of depression and anxiety symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to other study results, workplace violence causes fear-mediated turnover intentions and physical symptoms in the victims [ 33 ], which is similar to a study case that reported workplace bullying caused sleep disturbance mediated by negative affectivity, need for recovery, and worry [ 34 ]. Moreover, sleep disturbance has a bidirectional relationship with depression in that it is an outcome of depression as well as a risk factor of depression [ 35 ] and considering the fact that workplace violence is significantly correlated with depression [ 4 ], workplace violence can affect manifestation of sleep disturbance symptoms in people who experienced workplace violence, mediated by negative emotions, such as depression or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace violence is closely associated with mental health of the workers, and is a serious problem which can have a negative effect on individual workers [ 4 ]. Victims of workplace violence can manifest symptoms of somatization, depression, anxiety, and negative affectivness and even witnesses of workplace violence have been reported to show symptoms such as anxiety [ 5 ].…”
Section: Introductionmentioning
confidence: 99%